THE ROLE OF SIRAA VYADHANA IN TREATING GRIDHRASI - Puripanda, *S.Kamalakar; Renuka, M; Vaidya, SM.; Chetan, M (AYUSHDHARA, 2016)
The disease Gridhrasi is commonly seen in society as a prominent problem; in this condition patient will be incapable to do daily routine work. Symptoms initially affect Sphik as well as posterior aspect of Kati and then gradually radiates to posterior aspects of Uru, Janu, Jangha and Pada. In the Chikitsa Sutra of Gridhrasi Acharya Charaka, Sushruta, Vagbhatta, Yogratnakara and Bhela have mentioned Siraa Vyadhana why because Siraa Vyadhana removes Avarana as well as vitiated Doshas through Raktha and it also helps in decrease the pain. Dushya (Rakthadhi) should be treated and in turn Dosha (Vaatadhi) can be brought to normalcy. In Saakhanusari (Chronic) condition Siraa Vyadhana is very effective. In present era quick pain relief is of prime importance to resume normal activities. Hence Siraa Vyadhana is considered as instant reliever of pain. The main aim of the Siraa Vyadhana is Prakupita Dosha Nirharana and Sroto Shodhana. Present paper highlights the concept and effect of Siraa Vyadhana in Gridhrasi.